Hygienic Assessment of Harmful Factors and Prevention of Occupational Respiratory Diseases in Livestock Workers - H.O.Kosimov (American Journal of Biology and Natural Sciences, 2024)
The article considers the main factors of occupational risk of respiratory diseases in livestock workers (cattle breeding, pig breeding), analyses the dynamics and structure of occupational morbidity, scientifically substantiates hygienic principles of occupational health risk management for this category of workers, and recommends primary and secondary prevention of occupational respiratory diseases.